The Influence of Parenting Styles on Students Learning Motivation Akidah Akhlak Subject at MI Al Muttaqin - Agung Madani; Iskandar Yusuf (Yayasan Insan Mulia Bima, 2024)
The purpose of this study is to investigate how parenting styles affect students' motivation to learn during Akidah Akhlak lessons at MI AL Mutaqqin Balikpapan . The methodology is quantitative, and questionnaires and interviews are utilized to gather data. 42 students participated in this survey as respondents. The first result of the F value counted at 119,549 with a significance level of 0,000 < 0.05 which shows that the value 0,000 is less than 0.05 supports this theory and leads to the conclusion that the pattern of parental care affects learning motivation. Furthermore, the second result of a significant value of 0.000 < 0.05, which is produced based on the significance value of the coefficient table, shows that parental custody patterns influence student learning incentives. The data analysis results indicate that parenting styles have a major impact on students' motivation to learn in Akidah Akhlak sessions. This research suggests that parental parenting styles, particularly when it comes to religious issues, play a significant influence in raising students' willingness to learn.